Komparasi Simulasi CFD Pada Turbin Cross-Flow Dengan Model Turbulen k-ε STD dan RNG k-ε - Juan Setiawan; Steven Darmawan; Harto Tanujaya (Fakultas Teknik Universitas Pancasila, 2022)
The cross-flow turbine is one of widely used impulse turbine in power generator system due to it’s simple design and ability to be applied to a wide range of head and flow conditions. The flow in a cross-flow turbine flows in a crossed manner and works in 2 stages which could affect the turbine’s performance. Hence the visualization of these flow behavior could indicate the performance. Complexity of the flow inside the runner require the usage of CFD Method to visualize the flow, leaving the gap since numerical model also rely on turbulence model. The purpose of this study is to analyze the flow pattern in the nozzle and runner on a cross-flow turbine using the RNG k-ε turbulence model in ANSYS 2021 R2 Academic Version software. The simulation was carried out with 5 variations of nozzle inlet velocity: 2 m/s, 3 m/s, 4 m/s, 5 m/s and 6.487 m/s. The working fluid is assumed to be 1 phased water, with nozzle inlet pressure of 1.05 Pa, temperature of 24.85 oC and RNG k- ε turbulence model which compared to STD k-e turbulence model from the previous study. The results show that the simulation with the RNG k-ε turbulent models resulted in differences in the velocity and pressure profiles of Stage 1 of 3.353% and 87.679% and Stage 2 of 13.653% and 21.826% compared to simulation with k-ε STD models.